FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR SISWA JURUSAN IPS MATA PELAJARAN EKONOMI KELAS XI SMA N 6 SIJUNJUNG - Wahyuni, Tri; Akhirmen, Akhirmen; Areva, Desi (Pendidikan Ekonomi, 2013)
AbstrackThe purpose of this study is (1) Determine the influence of students perceptions about the variety of teaching styles to students learning motivation of economic subjects majoring in social studies class XI SMA 6 Sijunjung. (2) Determine the influence of instructional media on the students motivation of economic subjects majoring in social studies class XI SMA 6 Sijunjung. (3) Determine the influence of discipline on students motivation to learn social studies department of economic subjects in class XI SMA 6 Sijunjung.  (4) Determine the influence of students perceptions about the variety of teaching styles, instructional media and learn the discipline of the students motivation majoring in social studies class XI economics subjects SMAN 6 Sijunjung.This research is descriptive and associative, population in this study were all students majoring in social studies classes XI SMA 6 Sijunjung as many as 79 people. The samples are 66 people with the proportional random sampling method. Primary data and secondary data that has been collected is then statistically analyzed with descriptive and inductive analysis through multiple regression analysis using SPSS version 16.0.Results of the analysis of data obtained that (4) There is a significant influence on students perceptions of variety of teaching styles, instructional media and learn discipline together on motivation to learn the sig of 0.000, which is smaller than α = 0.05. (1) There is a significant influence on students perceptions of variety of teaching styles on motivation to learn with sig for 0.030 < 0.05 0.366 level influences. (2) There is no significant impact on students perceptions of instructional media on motivation to learn the sig of 0.406 > 0.05 with a 0.127 degree of influence. (3) there is a significant influence on motivation to learn the discipline of learning to sig 0.00 <0.05 with a 0.571 degree of influence.Based on the above results it can be concluded that a variety of teaching styles and learning discipline are two factors that can impact the motivation to learn . While learning media does not affect students motivation . It is thus suggested to students majoring in social studies class XI economics subjects SMA N 6 Sijunjung to increase again to learn discipline and to teachers in order to increase the variety of teaching styles to the learning process. Keywords : Variations in style of teaching , learning media , learning discipline        and motivation